Effects of spans and heights of half-cuboctahedron tensegrity roof subjected to wind loading - Nabihah Jamal,; Oh, Chai Lian; Mohd Raizamzamani Md Zain,; Lee, Siong Wee; Norrul Azmi Yahya, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Tensegrity structures are a type of structural system that consists of a specific set of cables connected to a rigid body configuration and stabilised by internal cable forces in the absence of external forces. Since tensegrity structures appear in lightweight features, wind-induced vibrations in roof structures increase the importance of structural design. Thus, this study analysed the effect of heights and spans towards half-cuboctahedron tensegrity roof model subjected to wind loading. The proposed grid’s heights are 0.5m, 1,0m and 1,5m. To conduct this study, the basic component of half-cuboctahedron consists of 12 cables and 4 struts were modelled first by using SAP2000 software. The basic model has been extended into another 4 units for the short span (2x2) model and another 16 units (4x4) for a long span model. The design parameters such as material and section properties, supports and loads subjected to the structure have been proposed as the provision laid down in Eurocode Standard. This study found that the deflection decreased apparently from a height of 0.5 m to 1.0 m up to about 40%. Analysis reveals that the span length is a more critical factor in determining deflection compared to the model’s height. An analysis of varying strut diameters was conducted to assess their impact on the demand capacity ratio. The findings demonstrated a decrease in diameter led to a higher demand capacity ratio. From the evaluation, struts with diameter 48.3 mm is the optimum size to be used for tensegrity roof model. The study provides understanding of the behaviour of tensegrity roof grid model subjected to wind loading.